Initial analysis of the available support programs for medium and large enterprises during the Covid-19 pandemic - Meloun, Tomáš; Kopkáně, Heřman; Lodr, Jakub; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2021)
The Covid-19 pandemic was an event on a global scale that had a negative impact on almost every society and economy of the world. The various governmental safety precautions and the economic crisis meant that many businesses had no way of generating income. Governments worldwide introduced financial support programs to help businesses survive. This paper aims to describe the programs that were available to Czech medium and large enterprises in the beginning months of the pandemic. The author also analyzes these programs by looking at available data and comparing them to similar programs in other countries. However, not all companies were eligible to receive financial aid. Correspondingly, the author also describes intercompany solutions to improve a company’s overall liquidity position. Finally, the author summarizes the discussed topics and briefly presents his outlook of the future economic situation.
Vedoucí práce: Heřman Kopkáně
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: business administration/corporate finance and management [obor bakal. práce]; bakalářské práce; bachelor's theses